The Effect of Firm Characteristics on the Voluntary Disclosures of Intellectual Capital in Annual Report (Case Study on Banking Sector Companies Registered on The Indonesia Stock Exchange) - Yulindisti, Elga (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2020)
The aim of this research study is to know whether profitability have significant effect on intellectual capital disclosure. The methodology using quantitative approach and the data is used secondary data. This research are used 50 annual reports of banking sector companies registered on Indonesia Stock Exchange as samples. The independent variable is profitability measured using Return of Equity and dependent variable is intellectual capital disclosure measure by Intellectual Capital Disclosure Index. This research used is simple linier regression analysis and the data testing is conducted by using SPSS 25. The results shown the profitability which is one of firm characteristics has no significant effect on voluntary of intellectual capital disclosure. Keywords: profitability, Firm characteristics, intellectual capital, voluntary disclosure REFERENCESBontis, N. (1998). Intellectual capital: an exploratory study that develops measures and models. Management Decision, 36(2), 63